Sustainability Status of Pond Aquaculture in Tambakbulusan Village on Social or Cultural Dimension and Legal or Institutional Dimension - Agry, Firdausa Putra; Purnomo, Pujiono Wahyu; Elfitasari, Tita (The Islamic Education and Multiculturalism Foundation, 2023)
Sustainability in the management of aquaculture activities is very important because it will make the welfare of the stakeholders. The research objectives initiated in the context of this discussion include several things, 1) Analyzing the status or index of sustainability that extends to other dimensions including social or cultural, and legal in relation to aquaculture ponds in Tambakbulusan Village Karangtengah District Demak Regency, 2) Knowing what are the sensitive attributes (levers) that affect the sustainability of aquaculture in Tambakbulusan village. The benefits of research is expected to provide benefits to the provision of comprehensive information, especially for stakeholders will describe the status of the sustainability of aquaculture ponds Tambakbulusan village. The implementation time of the research is detailed in March to April 2023 with the chosen setting is Tambakbulusan Village, Karangtengah District, Demak Regency. The determination of methods related to data analysis is with quantitative methods assisted by qualitative data results. The data obtained came from primary and secondary data. Primary data were collected from direct observations and interviews in the field with 47 (forty-seven) respondents. The analysis used is Multidimensional Scalling Rapid Appraisal for Fisheries (MDS-RAPFISH) to analyze several aspects or dimensions of sustainability. The results of the sustainability analysis obtained are in the social or cultural dimension of 61.441 including also quite sustainable and in the legal or institutional dimension of 42.909 including less sustainable. Sensitive attributes in the social or cultural dimension are the attributes of participation in development forums, labor absorption, and family participation in aquaculture, and in the legal or institutional dimension, sensitive attributes are known to include the attributes of the intensity of law violations in relation to aquaculture, the existence of financial institutions, the availability of cultivator groups, and the existence of customary or religious law instruments.